Effect of discharges of Shatt al-Arab river on total catch in Iraqi marine waters in north Gulf: Audai mohamed- Hasn Qasim - Qasim, Audai Mohamed-Hasn (Journal of Kerbala for Agricultural Sciences, 2018)
Iraqi marine fisheries in north-west Arabian Gulf have been studied in order to knew relationship between discharge water from shatt Al-arab river and Iraqian marine catch during 2017. The present study identified the amounts of the water from Tigris to Shatt al-Arab for the period 2014-2016. The results showed annual discharges were 53.7, 39.1 and 49.9 m3/s respectively, the total annual fishing catch recorded 5553, 3391 and 3992 tan for the years 2014, 2015 and 2016 respectively. The correlation between monthly quantities of fishing and catch per unit effort (CPUE) with the discharge of the Tigris river which entering the Shatt al-Arab was weak positive that indicating in the presence of different seasonal effects on fisheries type. The study revealed the strongest positive correlation between total annual catch and annual water discharges expenditure, as well as confirmed the impact of water discharges, ecosystem and climate change on quantity fisheries. In addition, the study illustrated the changing in discharges followed social and economic impacts. Our needing reform in fisheries policies and planning.